KOMPONEN SIM: PROSEDUR, BRAINWARE, DAN JARINGAN - Ridho Dwi Putra; Saipul Annur; Ade Rosad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Management Information Systems (MIS) are a crucial element in supporting decision-making and operational effectiveness of an organization. This study aims to analyze the main components of a Management Information System (MIS), including procedures, brainware, and networks. The research method used is a qualitative approach with literature studies and observations of MIS implementation in various organizations. The results show that structured procedures can improve workflow consistency and process efficiency. Brainware, as users and managers of the system, plays a crucial role in determining the success of MIS implementation, especially in terms of competence and technological adaptation. Meanwhile, the network functions as an infrastructure that supports the smooth exchange of data and information quickly and accurately. These three components are interrelated and must be managed in an integrated manner for MIS to run optimally. This study is expected to provide a more comprehensive understanding of the importance of integrating MIS components in supporting organizational performance.